Epoxy resin composite material and preparation process thereof
By constructing a porous airgel skeleton and using thermal conductive paths using modified boron nitride, the problem of reduced castability and reduced insulation performance of epoxy resin-based composite materials when increasing thermal conductivity is solved, achieving high thermal conductivity and excellent insulation. Performance balance.
Patent Information
- Application Number
- CN202411221686.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-21
AI Technical Summary
While the existing epoxy resin-based composite materials improve thermal conductivity, the castability decreases, and the increase in thermal filler will reduce insulation performance, making it difficult to take into account both thermal conductivity and insulation performance.
By constructing a porous airgel skeleton, using modified boron nitride to build a thermal conductive path, and using a binder to enhance the fastening between the airgel skeleton and modified boron nitride, the amount of thermally conductive materials can be reduced, and the performance of the composite material can be improved. Thermal conductivity and insulation properties.
It significantly improves the heat transfer rate of modified boron nitride, increases the thermal conductivity of epoxy resin composite materials, and enhances its insulation properties, solving the problem of balancing thermal conductivity and insulation properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin materials, and in particular to an epoxy resin composite material and a preparation process thereof. Background Art
[0002] Electrical and electronic equipment are constantly developing towards high power density and high integration, which leads to a sharp increase in the heat generation and temperature rise per unit volume of the equipment. Heat accumulation will accelerate the aging of insulation and seriously affect the reliability and life of the equipment. This puts higher requirements on the thermal conductivity and insulation performance of insulation materials.
[0003] In the prior art, the insulating materials of electrical and electronic equipment are mostly epoxy resin materials, but the thermal conductivity of epoxy resin is low. Usually, a thermally conductive filler with high thermal conductivity is added to epoxy resin to prepare an epoxy resin-based composite material to meet the heat dissipation requirements of electrical equipment. However, in order to meet the requirements of high thermal conductivity, the amount of thermally conductive filler added to the epoxy resin matrix is often large, and its castability will decrease, which is not conducive to the processing and molding of the composite material; at the same time, the use of metal or graphite thermal conductive materials, although it can improve the thermal conductivity of epoxy resin, will significantly reduce the insulation performance of epoxy resin, and cannot be effectively applied.
[0004] Therefore, how to reduce the amount of thermally conductive filler and improve the thermal conductivity and insulation properties of epoxy resin materials has become an urgent problem to be solved. Summary of the invention
[0005] In view of the defects in the prior art, the present invention proposes an epoxy resin composite material and a preparation process thereof, so as to solve the problem of how to improve the thermal conductivity and insulation properties of the epoxy resin material while reducing the amount of thermal conductive material.
[0006] In order to solve the above technical problems, this application provides the following technical solutions:
[0007] In a first aspect, the present application provides a process for preparing an epoxy resin composite material, comprising the following steps:
[0008] S1. Dispersing the modified boron nitride, the binder and the pore-forming agent in a sodium alginate solution to obtain a dispersion, freezing and freeze-drying the dispersion, and then thermally decomposing the pore-forming agent to obtain an aerogel skeleton;
[0009] S2. mixing the epoxy resin, curing agent and accelerator to obtain a mixture;
[0010] S3. Immerse the aerogel skeleton in the mixture and cure it by gradient heating to obtain the epoxy resin composite material.
[0011] Preferably, in step S1, the preparation method of the modified boron nitride is: mixing boron nitride nanosheets and dopamine, adding tris(hydroxymethyl)aminomethane to adjust the pH value to 8-9, and reacting to obtain the modified boron nitride.
[0012] Preferably, in step S1, the binder includes one or more of cellulose, polyvinyl butyral, and sodium silicate.
[0013] Preferably, in step S1, the pore-forming agent includes ammonium bicarbonate.
[0014] Preferably, in step S1, the freezing process is performed by freezing in a freezer at -10 to -60°C; and the freeze-drying process is performed by vacuum freeze-drying for 24 to 36 hours at ≤800Mpa and -30°C.
[0015] Preferably, in step S1, the temperature of thermal decomposition is 50-80°C.
[0016] Preferably, in step S2, the curing agent includes one or more of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, and the accelerator includes one or more of 2-ethyl-4-methylimidazole and N,N-dimethylbenzylamine.
[0017] Preferably, in step S3, the impregnation is vacuum impregnation, and the temperature of the vacuum impregnation is 20-50°C.
[0018] Preferably, in step S3, the step of gradient temperature curing is to pre-cure at a temperature of 60°C-80°C for 1-3 hours, and then cure at a temperature of 100°C-120°C for 4-10 hours.
[0019] In a second aspect, the present application provides an epoxy resin composite material.
[0020] In summary, compared with the prior art, the present invention achieves the following technical effects: the thermal conductive path constructed by the porous aerogel skeleton in the present application significantly improves the heat transfer rate of the modified boron nitride and improves the thermal conductivity of the epoxy resin composite material. At the same time, the porous structure allows the epoxy resin to be fully infiltrated, and the epoxy resin is more fully and deeply filled into the porous aerogel skeleton, thereby improving the insulation performance of the epoxy resin composite material. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0022] The present application provides a preparation process of an epoxy resin composite material, comprising the following steps:
[0023] S1. Dispersing the modified boron nitride, the binder and the pore-forming agent in a sodium alginate solution to obtain a dispersion, freezing and freeze-drying the dispersion, and then thermally decomposing the pore-forming agent to obtain an aerogel skeleton;
[0024] S2. mixing the epoxy resin, curing agent and accelerator to obtain a mixture;
[0025] S3. Immerse the aerogel skeleton in the mixture and cure it by gradient heating to obtain the epoxy resin composite material.
[0026] The present application uses a binder to connect the modified boron nitride and the pore-forming agent, obtains a solid intermediate after freeze drying, removes the pore-forming agent, obtains a porous aerogel skeleton, and then uses the aerogel skeleton as a carrier to load a mixture of epoxy resin, accelerator, and curing agent into the aerogel skeleton to obtain an epoxy resin composite material. The epoxy resin composite material obtained by the above method has a heat conduction path constructed by modified boron nitride, and the binder enhances the tightness between the aerogel skeleton and the modified boron nitride, which is conducive to reducing the amount of modified boron nitride and reducing the thermal resistance of the interface; the heat conduction path constructed by the porous aerogel skeleton in the present application can significantly improve the heat transfer rate of the modified boron nitride and improve the thermal conductivity of the composite material. At the same time, the porous structure can fully infiltrate the epoxy resin, and the epoxy resin is more fully and deeply filled into the porous aerogel skeleton, thereby improving the insulation performance of the composite material.
[0027] In some embodiments, in step S1, the preparation method of modified boron nitride is: mixing boron nitride nanosheets and dopamine, adding tris(hydroxymethyl)aminomethane to adjust the pH value to 8-9, and reacting to obtain modified boron nitride. The mass ratio of boron nitride nanosheets, dopamine, and tris(hydroxymethyl)aminomethane is 100:(20-50):(10-30).
[0028] In the present application, the modified boron nitride is a boron nitride nanosheet coated with polydopamine, which is beneficial to improving the compatibility of boron nitride with epoxy resin, making boron nitride less likely to agglomerate and improving thermal conductivity.
[0029] In some embodiments, in step S1, the binder includes one or more of cellulose, polyvinyl butyral, and sodium silicate.
[0030] In the present application, ammonium bicarbonate as a pore-forming agent can be decomposed at 50-80°C, and the pyrolysis temperature is low, which reduces energy consumption.
[0031] In some embodiments, in step S1, the freezing process is performed by freezing in a freezer at -10 to -60°C; and the freeze-drying process is performed by vacuum freeze-drying for 24-36 hours at ≤800Mpa and -30°C.
[0032] In some embodiments, in step S1, the temperature of thermal decomposition is 50-80°C.
[0033] In some embodiments, in step S2, the curing agent includes one or more of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, and the accelerator includes one or more of 2-ethyl-4-methylimidazole and N,N-dimethylbenzylamine.
[0034] In the present application, the epoxy resin includes one or more of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, and novolac epoxy resin.
[0035] In some embodiments, in step S3, the impregnation is vacuum impregnation, and the temperature of the vacuum impregnation is 20-50°C.
[0036] In some embodiments, in step S3, the step of gradient temperature curing is to pre-cure at a temperature of 60°C-80°C for 1-3 hours, and then cure at a temperature of 100°C-120°C for 4-10 hours.
[0037] In some embodiments, the weight ratio of the modified thermally conductive filler, the binder, the pore-forming agent and the sodium alginate is (5-10): (0.5-2): (1-5): 100; the mass ratio of the epoxy resin and the modified thermally conductive filler is 100: (5-10); the mass ratio of the epoxy resin, the curing agent and the accelerator is 100: (50-80): (0.8-2); although the amount of the modified thermally conductive filler added in the present invention is relatively small, the thermal conductivity of the epoxy resin composite material of the present invention is still excellent and can have excellent insulation properties.
[0038] In a second aspect, the present application provides an epoxy resin composite material.
[0039] Example 1
[0040] A preparation process of an epoxy resin composite material comprises the following steps:
[0041] S1. Disperse 5 g of modified boron nitride, 1 g of cellulose, and 2 g of ammonium bicarbonate in an aqueous solution containing 100 g of sodium alginate, stir evenly to obtain a dispersion, freeze the dispersion at -20 ° C in a freezer, and then vacuum freeze-dry for 24 h at 800 MPa and -30 ° C to obtain a solid, heat the solid at 80 ° C for 2 h to obtain an aerogel skeleton;
[0042] S2. 100 g of bisphenol A epoxy resin, 50 g of methyltetrahydrophthalic anhydride and 2 g of 2-ethyl-4-methylimidazole were mixed to obtain a mixture;
[0043] S3. The aerogel skeleton is vacuum impregnated into the mixture at 20°C, and cured by gradient temperature increase. The procedure of gradient temperature increase curing is: pre-curing at 60°C for 1h, and then curing at 100°C for 4h, to obtain the epoxy resin composite material.
[0044] Among them, the preparation method of modified boron nitride is: mix boron nitride nanosheets and dopamine, then add tris(hydroxymethyl)aminomethane to adjust the pH value to 8, and react at 30°C for 5 hours to obtain modified boron nitride. The mass ratio of boron nitride nanosheets, dopamine, and tris(hydroxymethyl)aminomethane is 100:50:10.
[0045] Example 2
[0046] A preparation process of an epoxy resin composite material comprises the following steps:
[0047] S1. Dispersing 10 g of modified boron nitride, 1 g of polyvinyl butyral ester, and 2 g of ammonium bicarbonate in an aqueous solution containing 100 g of sodium alginate, stirring evenly to obtain a dispersion, freezing the dispersion at -20 ° C in a freezer, and then vacuum freeze-drying at 800 MPa and -30 ° C for 24 h to obtain a solid, heating the solid at 80 ° C for 2 h to obtain an aerogel skeleton;
[0048] S2. 100 g of bisphenol A epoxy resin, 80 g of methyl hexahydrophthalic anhydride and 2 g of N, N-dimethylbenzylamine were mixed to obtain a mixture;
[0049] S3. The aerogel skeleton is vacuum impregnated into the mixture at 20°C, and cured by gradient temperature increase. The procedure of gradient temperature increase curing is: pre-curing at 80°C for 3h, and then curing at 120°C for 10h to obtain the epoxy resin composite material.
[0050] Among them, the preparation method of modified boron nitride is: mix boron nitride nanosheets and dopamine, then add tris(hydroxymethyl)aminomethane to adjust the pH value to 9, and react at 30°C for 5 hours to obtain modified boron nitride. The mass ratio of boron nitride nanosheets, dopamine, and tris(hydroxymethyl)aminomethane is 100:40:20.
[0051] Example 3
[0052] A preparation process of an epoxy resin composite material comprises the following steps:
[0053] S1. 20 g of modified boron nitride, 1 g of cellulose, and 2 g of ammonium bicarbonate were dispersed in an aqueous solution containing 100 g of sodium alginate, and stirred evenly to obtain a dispersion. The dispersion was frozen in a freezer at -20 ° C, and then vacuum freeze-dried at 800 MPa and -30 ° C for 24 h to obtain a solid. The solid was heated at 80 ° C for 2 h to obtain an aerogel skeleton;
[0054] S2. 100 g of bisphenol A epoxy resin, 50 g of methyltetrahydrophthalic anhydride and 2 g of 2-ethyl-4-methylimidazole were mixed to obtain a mixture;
[0055] S3. The aerogel skeleton is vacuum impregnated into the mixture at 20°C, and cured by gradient temperature increase. The procedure of gradient temperature increase curing is: pre-curing at 60°C for 1h, and then curing at 100°C for 4h, to obtain the epoxy resin composite material.
[0056] Among them, the preparation method of modified boron nitride is: mix boron nitride nanosheets and dopamine, then add tris(hydroxymethyl)aminomethane to adjust the pH value to 8, and react at 30°C for 5 hours to obtain modified boron nitride. The mass ratio of boron nitride nanosheets, dopamine, and tris(hydroxymethyl)aminomethane is 100:50:10.
[0057] Comparative Example 1
[0058] A preparation process of an epoxy resin composite material comprises the following steps:
[0059] S1. Disperse 5 g of boron nitride, 1 g of cellulose, and 2 g of ammonium bicarbonate in 100 g of an aqueous solution containing 100 g of sodium alginate, stir evenly to obtain a dispersion, freeze the dispersion at -20 ° C in a freezer, and then vacuum freeze-dry for 24 h at 800 MPa and -30 ° C to obtain a solid, heat the solid at 80 ° C for 2 h to obtain an aerogel skeleton;
[0060] S2. 100 g of bisphenol A epoxy resin, 50 g of methyltetrahydrophthalic anhydride and 2 g of 2-ethyl-4-methylimidazole were mixed to obtain a mixture;
[0061] S3. The aerogel skeleton is vacuum impregnated into the mixture at 20°C, and cured by gradient temperature increase. The procedure of gradient temperature increase curing is: pre-curing at 60°C for 1h, and then curing at 100°C for 4h, to obtain the epoxy resin composite material.
[0062] Comparative Example 2
[0063] A preparation process of an epoxy resin composite material, the other contents of which are the same as those of Example 1, except that ammonium bicarbonate is not included.
[0064] Test and Evaluation
[0065] The epoxy resin composite materials obtained in the examples and comparative examples were tested, and the results are shown in Table 1. The test contents are as follows:
[0066] Thermal conductivity test: The thermal conductivity was tested using the German NETZSCH LFA467 laser flash thermal conductivity meter. According to the ASTM1461 standard, the sample thickness was 1mm±0.1mm.
[0067] Volume resistivity test: Tested in accordance with the standard of GB8815-2002.
[0068] Table 1 Test results of various composite materials
[0069]
[0070] The present application uses a binder to connect the modified boron nitride and the pore-forming agent, obtains a solid intermediate after freeze drying, removes the pore-forming agent, obtains a porous aerogel skeleton, and then uses the aerogel skeleton as a carrier to load a mixture of epoxy resin, accelerator, and curing agent into the aerogel skeleton to obtain an epoxy resin composite material. The epoxy resin composite material obtained by the above method has a heat conduction path constructed by modified boron nitride, and the binder enhances the tightness between the aerogel skeleton and the modified boron nitride, which is conducive to reducing the amount of modified boron nitride and reducing the thermal resistance of the interface; the heat conduction path constructed by the porous aerogel skeleton in the present application can significantly improve the heat transfer rate of the modified boron nitride and improve the thermal conductivity of the composite material. At the same time, the porous structure can fully infiltrate the epoxy resin, and the epoxy resin is more fully and deeply filled into the porous aerogel skeleton, thereby improving the insulation performance of the composite material.
[0071] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing an epoxy resin composite material, characterized in that: The following steps are involved: S1. dispersing the modified boron nitride, the binder and the pore-forming agent in the sodium alginate solution to obtain a dispersion, freezing and freeze-drying the dispersion, and then thermally decomposing the pore-forming agent to obtain an aerogel skeleton; S2. mixing the epoxy resin, curing agent and accelerator to obtain a mixture; S3. Immersing the aerogel skeleton in the mixture, and curing the mixture by gradient heating to obtain the epoxy resin composite material.
2. The preparation process of the epoxy resin composite material according to claim 1, characterized in that: In step S1, the preparation method of the modified boron nitride is: mixing boron nitride nanosheets and dopamine, adding tris(hydroxymethyl)aminomethane to adjust the pH value to 8-9, and reacting to obtain the modified boron nitride.
3. The preparation process of the epoxy resin composite material according to claim 1, characterized in that: In step S1, the binder includes one or more of cellulose, polyvinyl butyral, and sodium silicate.
4. The preparation process of the epoxy resin composite material according to claim 1, characterized in that: In step S1, the pore-forming agent includes ammonium bicarbonate.
5. The process for preparing the epoxy resin composite material according to claim 1, characterized in that: In step S1, the freezing process is performed by freezing in a freezer at -10 to -60°C; and the freeze-drying process is performed by vacuum freeze-drying for 24 to 36 hours at ≤800Mpa and -30°C.
6. The process for preparing the epoxy resin composite material according to claim 1, characterized in that: In step S1, the temperature of the thermal decomposition is 50-80°C.
7. The process for preparing the epoxy resin composite material according to claim 1, characterized in that: In step S2, the curing agent includes one or more of methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, and the accelerator includes one or more of 2-ethyl-4-methylimidazole and N,N-dimethylbenzylamine.
8. The process for preparing the epoxy resin composite material according to claim 1, characterized in that: In step S3, the impregnation is vacuum impregnation, and the temperature of the vacuum impregnation is 20-50°C.
9. The process for preparing the epoxy resin composite material according to claim 1, characterized in that: In step S3, the step of gradient temperature curing is to pre-cure at a temperature of 60°C-80°C for 1-3 hours, and then cure at a temperature of 100°C-120°C for 4-10 hours.
10. An epoxy resin composite material obtained by the preparation process according to any one of claims 1 to 9.
Citation Information
Cited By
High-thermal-conductivity and high-temperature-resistant electronic molding compound and preparation method thereof
CN121136342A